Transformasi UMKM Desa Manggungsari melalui Pemasaran Kreatif, Digitalisasi, dan Legalitas - Sudiarti, Sri; Khodijah, Amalia Siti; Asih, Lilik Suci; Nurjanah, Wulan Zahra; Romalah, Iis; Husni, Nurul Fauziah; Aulya, Surya Ardiansyah; Mulyana, Yayan; Karlina, Leni (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to empower MSMEs in Manggungsari Village by strengthening creative marketing, digitalization, and business legality. The main problems faced by partner MSMEs include limited branding strategies, low digital literacy, and lack of business legality. The method applied was a participatory approach consisting of planning, action, observation, and reflection stages. The results indicate improvements in product identity through logo and packaging designs, market expansion through Google Maps mapping and online store creation, and business legality with 24 enterprises obtaining Business Identification Numbers (NIB) and 2 enterprises receiving halal certification. Challenges encountered include limited devices, unstable internet connectivity, and technical barriers in the legalization process. Overall, this program successfully enhanced awareness, skills, and formal legality of MSMEs in Manggungsari Village, providing a foundation for more professional and sustainable business development.